2018
DOI: 10.1097/md.0000000000010971
|View full text |Cite
|
Sign up to set email alerts
|

Curative efficacy and safety of traditional Chinese medicine xuebijing injections combined with ulinastatin for treating sepsis in the Chinese population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Xuebijing injection, a patented TCM developed for the treatment of SARS in China, is indicated for infection-associated SIRS. The results of a meta-analysis of 16 papers, including 1335 cases of sepsis in a Chinese population, showed that, compared with ulinastatin alone, the combination of Xuebijing with ulinastatin led to a shorter mechanical ventilation time, shorter ICU stay, improved 28-day survival rate, reduced incidence of MODS and mortality, decreased procalcitonin concentration, ameliorated acute physiology and chronic health evaluation (APACHE) II score, and reduced levels of TNF-α and IL-6 ( 94 ). Xuebijing also exhibited antithrombotic activity, which could prevent vascular embolism caused by COVID-19 ( 91 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…Xuebijing injection, a patented TCM developed for the treatment of SARS in China, is indicated for infection-associated SIRS. The results of a meta-analysis of 16 papers, including 1335 cases of sepsis in a Chinese population, showed that, compared with ulinastatin alone, the combination of Xuebijing with ulinastatin led to a shorter mechanical ventilation time, shorter ICU stay, improved 28-day survival rate, reduced incidence of MODS and mortality, decreased procalcitonin concentration, ameliorated acute physiology and chronic health evaluation (APACHE) II score, and reduced levels of TNF-α and IL-6 ( 94 ). Xuebijing also exhibited antithrombotic activity, which could prevent vascular embolism caused by COVID-19 ( 91 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…Rhubarb, astragalus, Polygonum cuspidatum, asiatica, motherwort , and Ligusticum chuanxiong and their effective extracts can significantly reduce the levels of various inflammatory factors such as TNF‐α and IL‐6, maintain redox reaction, promote the excretion of blood urea nitrogen (BUN) and serum creatinine (Scr), reduce the renal injury, and protect the renal function . TCM compounds, Qingwenbaidu and Xuebijing injection, control the excessive release of inflammatory factors and cytokines by clearing heat, detoxifying the blood circulation, removing the blood stasis, restoring the balance of pro‐inflammatory and anti‐inflammatory reactions, reducing the injury of tissues and organs to the maximum, and protecting the normal functions of the kidney .…”
Section: Therapeutic Principle Of Infectious Diseases In Tcmmentioning
confidence: 99%
“…However, macrolide resistance has emerged worldwide with a significant increase, which increasingly lead to complex clinical treatment schemes . In recent years, with the increase of people’ recognition of traditional Chinese medicine, combining Chinese Medicine and Western Medicine to treat diseases has been an acceptable treatment method . This provides another idea to treat mycoplasma pneumonia in children.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…2,[11][12][13][14][15] In recent years, with the increase of people' recognition of traditional Chinese medicine, combining Chinese Medicine and Western Medicine to treat diseases has been an acceptable treatment method. 16,17 This provides another idea to treat mycoplasma pneumonia in children.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%